Forever young: rejuvenating muscle satellite cells - Madaro, Luca (Front Aging Neurosci, 2015)
A hallmark of aging is alteration of organismal homeostasis and progressive decline of tissue functions. Alterations of both cell intrinsic functions and regenerative environmental cues contribute to the compromised stem cell activity and reduced regenerative capability occurring in aged muscles. In this perspective, we discuss the new evidence supporting the hypothesis that skeletal muscle stem cells (MuSCs) are intrinsically defective in elderly muscles. In particular, we review three recent papers leading to identify fibroblast growth factor receptor-1, p38 mitogen-activated protein kinase, and p16INK4a as altered signaling in satellite cells from aged mice. These pathways contribute to age-related loss of MuSCs asymmetric polarization, compromised self-renewal capacity, and acquisition of pre-senescent state. The pharmacological manipulation of those networks can open novel strategies to rejuvenate MuSCs and counteract the functional decline of skeletal muscle during aging.